Globalisation and Agricultural Diversification of India - Roy, Pashupati Kumar; Economic Association of Bihar. Conference 2009 : T.M. Bhagalpur University); Roy, Pashupati Kumar; Sharma, Shiw Pershan; Tilka Manjhi Bhagalpur University (New Delhi : Regal Publications, 2010)
Papers presented at the 12th Annual Conference of Economic Association of Bihar, held at T.M. Bhagalpur University, during July 4-6, 2009.
pt. 1. Agricultural diversification in Indian perspective -- pt. 2. Agricultural diversification and sustainable development -- pt. 3. Gender issue and agricultural diversification -- pt. 4. Agricultural diversification of Bihar and Jharkhand -- pt. 5. Diversification of horticulture and allied sectors of agriculture.
Includes bibliographical references and index.
Keywords: Agricultural diversification -- India -- Congresses; Agriculture -- Economic aspects -- India -- Congresses; Globalization -- Economic aspects -- India -- Congresses; Agricultural diversification -- India -- Bihar -- Congresses